Hypoglycemia during Short-Term Intensive Insulin Therapy and Its Association with Long-Term Glycemic Remission in Patients with Newly Diagnosed Type 2 Diabetes - Lijuan Xu; Pengyuan Zhang; Zhimin Huang; Liangying Zhong; Hai Li; Liehua Liu; Juan Liu; Haipeng Xiao; Yanbing Li (Journal of Diabetes Research)
Background. Short-term intensive insulin therapy induces long-term glycemic remission in half of patients with newly diagnosed type 2 diabetes. The concomitant hypoglycemia needs further analysis. Methods. We collected data from three randomized trials conducted with the same inclusion and exclusion criteria at our institution from 2002 to 2015. Continuous subcutaneous insulin infusion (CSII) was provided to achieve the glycemic goals within a week and then maintained for 14 days. Hypoglycemia episodes during short-term treatment and the one-year drug-free glycemic remission were observed. Results. A total of 244 patients were included. The per day episode of mild hypoglycemia (3.0-3.9 mmol/L) was higher in the remission group than in the nonremission group (0.26±0.20 vs. 0.18±0.21, P=0.005). However, a moderate hypoglycemia episode (<3.0 mmol/L) per day was insignificantly lower in the remission group (0.02±0.04 vs. 0.03±0.04, P=0.221). After the cessation of insulin treatment, both acute insulin response (491.35 (801.89) vs. 370.22 (542.29), P=0.028) and homeostasis model assessment of insulin resistance (2.08 (2.04) vs. 2.48 (2.32), P=0.038) were more improved in the remission group than in the nonremission group. Logistic regression analysis showed that mild hypoglycemic episodes during short-term CSII treatment were independently related to a long-term glycemic remission (OR=2.18, 95% CI 1.02~4.70). Stratified analysis demonstrated that episodes during the continuing insulin dose reduction period played a substantial role. Conclusions. Mild hypoglycemic episodes during the continuing insulin dose reduction period indicate a long-term drug-free euglycemic remission in patients with newly diagnosed type 2 diabetes. However, the insulin dosage should be reduced even more quickly in the future treatment to decrease the potential harms.